MUC1, MUC2, MUC4, MUC5AC, Cdx2: immunohistochemical characteristics in polyps and adenocarcinoma of distal colon - M. A. Shyshkin (Zaporozhye State Medical University, 2019)
Aim - to study MUC1, MUC2, MUC4, MUC5AC, Cdx2 immunohistochemical expression in polyps and adenocarcinoma of distal colon. Materials and methods. Pathomorphological and immunohistochemical studies of biopsies from 30 patients, which underwent colonoscopy with polypectomy, and surgical material from 30 patients, which underwent surgery for colorectal adenocarcinoma, were carried out. Results. Distal colonic polyps are different from unchanged mucosa by increased MUC-1 expression. Maximum expression levels of the marker are observed in serrated adenomas, which are characterized by high MUC-1 expression level. Median of MUC-1 expression in adenocarcinoma is greater than that in unchanged mucosa, however, less than in polyps. Comparative analysis of data of the study of MUC2 expression indicates that the maximum expression of the marker is characteristic of unchanged mucous membrane. Polyps are distinguished by lower MUC2 expression levels; among them, highest expression levels are observed in hyperplastic polyps, lesser - in serrated adenomas and adenomas. Distal colonic carcinoma has extremely low median of MUC2 expression. The highest levels of MUC4 expression are observed in hyperplastic polyps, somewhat lower - in unchanged mucosa. Serrated adenomas, adenomas and adenocarcinomas differs by lower MUC4 expression levels. The minimum level of the marker expression is observed in serrated adenomas. In polyps MUC5AC expression levels are greater than in adenocarcinoma. Expression of this marker is not detected in unchanged mucosa. The maximum median of MUC5AC expression is observed in serrated adenomas, which are characterized by high level of the marker expression, somewhat lower - in adenomas, and more lower in hyperplastic polyps. High Cdx-2 expression level characterizes serrated adenomas and adenocarcinoma. The average Cdx-2 expression level is observed in adenomatous polyps, hyperplastic polyps, and unchanged mucosa, with the medians of the marked expression decreasing in that sequence. Conclusions. Distal colon polyps are characterized by increased MUC1 and Cdx-2 expression levels, with parallel decrease of MUC2 expression level and aberrant MUC5AC expression. At the same time, serrated adenomas are distinguished by the greatest deviations of the studied markers expression levels. Adenocarcinoma of the distal colon, compared with polyps, is characterized by decrease of MUC1, MUC2 and MUC5AC expression levels.